Oral Health Promotion in Elderly Population - A Hajizamani; R Craven (Tehran University of Medical Sciences, 2005)
Objectives: The aims of the study were to assess current practice in oral health care among residential homes for the elderly in Manchester, Salford and Stockport and to evaluate the effectiveness of a programme to increase carers' knowledge in key areas. Methods: The study was part of a randomised control trial, conducted in 56 residential homes, allocated randomly to test and control groups matched using the minimisation method. Managers of participating homes were interviewed to gather baseline data on the homes and oral care provided. A training session in oral health care for the elderly was provided for care staff in the homes. Carers` knowledge was assessed before and after the training session and their perceptions of the training were sought. Results: The survey of mangers revealed common inadequacies: the lack of any training for care staff in oral care; the lack of protocols for oral care (at 68% of homes); the lack of initial oral assessment. After the training session, the oral health knowledge of carers (467 carers) showed a significant improvement (McNemar Test, P< 0.005). Conclusion: Current practice in most homes is inadequate. The training sessions improved the carers' knowledge in key areas but improvements in the organisation and delivery of care are clearly also required.